2019
DOI: 10.1039/c9ra06886d
|View full text |Cite
|
Sign up to set email alerts
|

Iron phosphide nanoparticles as a pH-responsive T1 contrast agent for magnetic resonance tumor imaging

Abstract: In this work, the potential of FeP nanoparticles as a pH-responsive T1 contrast agent was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The r 1 values are higher than those of other MRI contrast agents (FeP, Fe@MSNs, MnFe-LDH) and commercially available Gd contrast agents, such as Gd-DTPA and Gd-DOTA. [43][44][45][46][47] On the other hand, the r 2 images showed a clear Fe(III)-concentration dependent change from bright to dark, and the r 2 value was calculated to be 26.59 mM À1 s À1 , suggesting good sensitivity as a T 2 MRI contrast agent. The r 2 /r 1 ratio is estimated to be $2.7 in the range of 2-10, [48][49][50] indicating the simultaneous combination of the T 1 and T 2 contrast effects.…”
Section: Mri Performance Of Dual-fe/omcmentioning
confidence: 98%
“…The r 1 values are higher than those of other MRI contrast agents (FeP, Fe@MSNs, MnFe-LDH) and commercially available Gd contrast agents, such as Gd-DTPA and Gd-DOTA. [43][44][45][46][47] On the other hand, the r 2 images showed a clear Fe(III)-concentration dependent change from bright to dark, and the r 2 value was calculated to be 26.59 mM À1 s À1 , suggesting good sensitivity as a T 2 MRI contrast agent. The r 2 /r 1 ratio is estimated to be $2.7 in the range of 2-10, [48][49][50] indicating the simultaneous combination of the T 1 and T 2 contrast effects.…”
Section: Mri Performance Of Dual-fe/omcmentioning
confidence: 98%
“…FeP nanoparticles can product significantly enhanced T 1 magnetic resonance signals by releasing paramagnetic Fe ions under acidic TME stimulation. [ 6 ] Due to the excellent loading performance and good degradability of metal phosphate, the combination of metal phosphate nanomaterials and paramagnetic ions can obtain a metal phosphate‐based MRI contrast agent in response to pH stimulation. Moreover, Kataoka's group reported that confining Mn 2+ within pH‐sensitive PEG‐CaP NPs (PEGMnCaP) could achieve rapid amplification of MR signals in response to acidic pH value.…”
Section: Metal‐p Nms For Tumor Diagnosismentioning
confidence: 99%
“…[ 19 ] The excellent optical, magnetic, and catalytic properties make Metal‐P NMs can be used as multifunctional diagnostic (photoacoustic imaging (PAI), fluorescent imaging (FI), magnetic resonance imaging (MRI), and nuclear imaging) and therapeutic (photothermal therapy (PTT), chemodynamic therapy (CDT), photodynamic therapy (PDT), and immunotherapy) agents for tumor theranostics. [ 5–19 ] Moreover, Metal‐P NMs are also suitable to be nanocarriers for delivering drugs owing to their degradable properties. [ 12 ] As a good medicine carrier, Metal‐P NMs can be loaded on chemotherapy drugs, photosensitizers, sonosensitizers, Fenton agents, genes, proteins, and various imaging contrast agents to achieve the integration of multimodal imaging and therapies.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Qiu et al 65 synthesized novel FeP NPs with a pH-activatable T 1 -weighted MR signal. In the presence of an acidic microenvironment (pH = 5.5), nearly 60% of Fe 3+ ions were extracted, which is almost ten-fold that under neutral conditions (pH = 7.4).…”
Section: Ion Extractionmentioning
confidence: 99%
“…Hence, some designs based on valance changes of these diamagnetic ions have emerged. [61][62][63][64][65][66][67] For instance, Liu et al 68 (G) The T 1 -based assay for the detection of glucose in serum, urine, and saliva with different concentrations of glucose. Reproduced with permission.…”
Section: Valance Conversionmentioning
confidence: 99%